Intraspecific call variation in a Neotropical gladiator frog with a complex advertisement call - Turin, Rubens A. F. [UNESP]; Nali, Renato C.; Prado, Cynthia P. A. [UNESP] (Brill Academic Publishers, 2018)
Vocalisation is one of the most conspicuous behavioural traits in different animals, but its emission can be variable within species, depending on environmental, morphological, and/or social factors. Understanding how acoustic parameters vary can provide information about sexual selection mechanisms that might have shaped the species' evolutionary history. We quantified and compared the variation of five call parameters within and among the males of Bokermannohyla ibitiguara, a Neotropical treefrog with complex reproduction and advertisement calls. The parameters were classified as static (dominant frequency), intermediate (note durations) or dynamic (pulse rate of the long note and call duration). Despite these differences, all of them varied more among individuals than within individuals, and most were associated with individual discrimination, showing potential acoustic recognition by males and females. A multiple regression analysis showed that all temporal parameters were affected by abiotic factors, except pulse rate of the long note; body size affected dominant frequency, duration of the long notes and call duration. This high variability in parameters, and the strong support for individual discrimination, indicate the existence of sexual selection mechanisms operating on calls; however, the individual recognition system is very complex and not limited to a single characteristic of the call. This is supported by the reproductive behavior of this species, including choosy females, elaborate courtships, and male-male vocal contests and physical combats. Fine-scale playback experiments with males and females will help us further understand sexual selection mechanisms in this and other acoustically oriented animals.
Keywords: amphibia; behavioural ecology; bioacoustics; cerrado; individual discrimination; sexual selection